2017
DOI: 10.1186/s13014-017-0839-3
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated radiation therapy from 70Gy to 80Gy in prostate cancer: six- year outcomes and predictors of late toxicity

Abstract: ObjectiveTo report grade ≥2 overall late rectal and urinary toxicities in patients (pts) with prostate cancer treated by intensity-modulated radiotherapy (IMRT) at 3 dose-levels. Identify predictors of radiation toxicity and report biochemical progression free survival (bPFS).MethodsA total of 277 pts were treated with 70Gy (10.8%), 74Gy (63.9%) and 80 Gy (25.3%) using IMRT without pelvic irradiation were analyzed. Short or long-course androgen deprivation therapy (ADT) was allowed in 46.1% of pts. The toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…8 Recently, Hao Peng et al reported that the rate of CR and PR after three cycles of IC regimen of TPF were 11.3% and 79.6%, respectively, in a phase III clinical trial. 24,25 Therefore, it is necessary to investigate whether reduced-dose radiotherapy is feasible for NPC and how to reduce radiation dose. However, it was not possible to assess tumor response because these patients were not examined with MRI after IC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, Hao Peng et al reported that the rate of CR and PR after three cycles of IC regimen of TPF were 11.3% and 79.6%, respectively, in a phase III clinical trial. 24,25 Therefore, it is necessary to investigate whether reduced-dose radiotherapy is feasible for NPC and how to reduce radiation dose. However, it was not possible to assess tumor response because these patients were not examined with MRI after IC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…An organ with such an architecture is highly sensitive to small volumes receiving high doses. In the particular case of the urinary bladder, reducing the volume that receives more than 75-78 Gy or more than 8-12 Gy per week (5,9,11,12,15,26,27,34,(53)(54)(55) may significantly decrease the risk of acute and/or late urinary toxicity. Table II reports some details of trials highlighting the relationship between acute/late urinary toxicity and bladder doses/prescription dose (with prescription dose being a surrogate for dose to small bladder volumes).…”
Section: How Can We Optimize Radiotherapy Treatment Minimizing the Rimentioning
confidence: 99%
“…A first essential risk factor for urinary toxicity, consistently described by different trials, is the baseline urinary functionality (8,13,15,44,77,78), with patients having an already impaired functionality being at higher risk of experiencing severe acute and late urinary toxicity. For this reason, an evaluation of the baseline situation should be mandatory before treatment planning, also considering the possibility of stricter dose limits for some patients.…”
Section: Does the Individual Patient Matter? Clinical Features As Modmentioning
confidence: 99%
See 2 more Smart Citations